Bond between textile-reinforced mortar (TRM) and concrete substrates: experimental investigation - Raoof, Saad M.; Koutas, Lampros N.; Bournas, Dionysios A. (Elsevier, 2016)
This paper presents an extended experimental study on the bond behaviour between textile-reinforced mortar (TRM) and concrete substrates. The parameters examined include: (a) the bond length (from 50 mm to 450 mm); (b) the number of TRM layers (from one to four); (c) the concrete surface preparation (grinding versus sandblasting); (d) the concrete compressive strength (15 MPa or 30 MPa); (e) the textile coating; and (f) the anchorage through wrapping with TRM jackets. For this purpose, a total of 80 specimens were fabricated and tested under double-lap direct shear. It is mainly concluded that: (a) after a certain bond length (between 200 mm and 300 mm for any number of layers) the bond strength marginally increases; (b) by increasing the number of layers the bond capacity increases in a non-proportional way, whereas the failure mode is altered; (c) concrete sandblasting is equivalent to grinding in terms of bond capacity and failure mode; (d) concrete compressive strength has a marginal effect on the bond capacity; (e) the use of coated textiles alters the failure mode and significantly increases the bond strength; and (f) anchorage of TRM through wrapping with TRM jackets substantially increases the ultimate load capacity.